Effect of Palladium‐Tetrakis(Triphenylphosphine) Catalyst Traces on Charge Recombination and Extraction in Non‐Fullerene‐based Organic Solar Cells. (8th February 2021) - Schopp, Nora; Brus, Viktor V.; Lee, Jaewon; Dixon, Alana; Karki, Akchheta; Liu, Tuo; Peng, Zhengxing; Graham, Kenneth R.; Ade, Harald; Bazan, Guillermo C.; Nguyen, Thuc‐Quyen
Abstract: The effect of the cross‐coupling catalyst tetrakis(triphenylphosphine)palladium(0) (Pd(PPh3 )4 ) on the performance of a model organic bulk‐heterojunction solar cell composed of a blend of poly([2, 6′‐4, 8‐di(5‐ethylhexylthienyl)benzo[1, 2‐b;3, 3‐b]dithiophene]{3‐fluoro‐2[(2‐ethylhexyl)carbonyl]thieno[3, 4‐b]thiophenediyl}) (PTB7‐Th) donor and 3, 9‐bis(2‐methylene‐((3‐(1, 1‐dicyanomethylene)‐6, 7‐difluoro)‐indanone))‐5, 5, 11, 11‐tetrakis(4‐hexylphenyl)‐dithieno[2, 3‐d:2′, 3′‐d′]‐s‐indaceno[1, 2‐b:5, 6‐b′]dithiophene (IOTIC‐4F) non‐fullerene acceptor is investigated. The effect of intentional addition of different amounts of Pd(PPh3 )4 on morphology, free charge carrier generation, non‐geminate bulk trap‐ and surface trap‐assisted recombination as well as bimolecular recombination and charge extraction is quantified. This work shows that free charge carrier generation is affected significantly, while the impact of Pd(PPh3 )4 on non‐geminate recombination processes is limited because the catalyst does not facilitate efficient trap‐assisted recombination. The studied system shows substantial robustness towards the addition of Pd(PPh3 )4 in small amounts. Abstract : The effect of Pd cross‐coupling catalyst traces on the physical processes in a non‐fullerene bulk‐heterojunction solar cell is investigated. The drop of the solar cell performance upon addition of systematically added amounts of tetrakis(triphenylphosphine)palladium(0) is explained by alteration of the morphology, charge carrier generation, recombination, and charge extraction.